The Right to Menopause - María Ángeles Orts Llopis (Cultura, Lenguaje y Representación, 2024)
Menopause often leads to a dual form of discrimination rooted in age and gender. Frequently overlooked, the side effects of menopause compel many women to leave their jobs due to discrimination or the psychological and physical challenges hindering their work. Recent British legal rulings in favour of women claiming workplace discrimination indicate a growing recognition of menopause as an “invisible” factor contributing to women’s labour market exclusion in the UK. In Spain, despite approximately four million menopausal women, a 2020-2022 search in the Spanish legal database CENDOJ found limited evidence of those claiming disability or impairment due to menopause-related issues as obstacles to their work. This paper conducts an emotion discourse analysis (Koschut, 2018 and 2020) of a representative set of legal decisions in English and Spanish concerning menopause as a workplace hindrance. We aim to examine how employment courts perceive and address this disabling condition that affects women’s well-being and self-esteem. By analysing the macrostructure of both language subcorpora, we unveil the legal narrative and identify lexical characteristics and emotional undertones as linguistic and cognitive tools that stigmatize or ignore this temporary female condition. The present analysis sheds light on the positions taken by judges and the evaluations made by all parties involved in these cases.